Scanning electron microscopy of placental villi hydropic transformation - Castejón S., Olivar (2015)
Introduction: To investigate placental hydropic vesicles stromal transformation is important in determining pathophysiologic tissue alterations. Objectives: To describe hydatidiform mole and placental mesenchymal dysplasia tridimensional characteristics of villi stroma hydropic transformation. Design: Histopathologic study. Biologic material: Curettage specimens obtained from patients with molar pregnancy and placental mesenchymal dysplasia. Interventions: Conventional scanning electron microscopy stains were applied to specimens obtained by curettage from patients with molar pregnancy and placental mesenchymal dysplasia. Results were compared with normal villi. Both specimens were obtained during the second trimester of pregnancy. Main outcome measures: Placental hydropic villi stromal changes. Results: A complex net of cells and bundles of collagen fibres associated to extracellular matrix of loose connective tissue were observed as well as regions with cells close to each other. Cavities of different size resulted from stromal tissue  disappearance in dense stroma regions. Small spaces seemed to converge and constitute larger ones until a central cistern was developed. In some vesicles the stromal region was displaced to the periphery below the trophoblast internal layer central cistern enlargement that appeared empty where interstitial fluid existed in vivo. Frequently vesicles with large empty spaces replaced dense stroma. Conclusions: These findings give a new tridimensional vision of changes produced by fluid entrance into hydropic vesicles stroma resulting in an edematous structure and give us a better understanding of stromal hydropic transformation.